PEDAGOGICAL TECHNOLOGIES IN ACCORDANCE WITH THE SPECIFIC CHARACTERISTICS OF TEACHING AND THEIR DESCRIPTION - Turdimurodova Zarinabonu Zafarovna; Juraqulova, Surayyo Mamanazar qizi (American Journals, 2023)
This article provides information about pedagogical technologies and their description that are in accordance with the specific characteristics of teaching.
Keywords: Pedagogical technology, problem-based learning, base signals, ability, classical lecture, traditional education, alternative technology, verbal, non-verbal, audio, visual, model.